A symbolic reading of adrienne richs an unsaid word - Hassan, Mohamad Fleih; Hardev Kaur; Mani, Manimangai (SciPress, 2016)
An imitation of the literary styles and modes of expression of the great writers in the post-World War II was the criterion of success for any male or female writer. The conventions of T.S. Eliot and W.H. Auden influenced the poetics and thought of the younger generation poets. For example, Adrienne Rich (1929-2012) was an ardent disciple of these conventions in her early career. She was influenced by the phallogocentric discourse of subject formation. She followed this man-made discourse to be accepted within the literary circle as a successful woman writer, but she realized that this discourse didn't help women in the expression of their female voices. This study explores the failure of the phallogocentric techniques and modes of writing in the expression of Rich's female voice in An Unsaid Word (1951). The study is conducted in the light of Lacanian Symbolic system of identification. The study concludes that Lacanian system of identification was behind the distortions of meanings associated with women and the failure of the symbolic order in the self-expression of Rich's female character in her poem An Unsaid Word.